Fashion in European art : dress and identity, politics and the body, 1775-1925 - Young, Justine de (Dress cultures., 2017)
Fashion reveals not only who we are, but whom we aspire to be. From 1775 to 1925, artists in Europe were especially attuned to the gaps between appearance and reality, participating in and often critiquing the making of the self and the image. Reading their portrayals of modern life with an eye to fashion and dress reveals a world of complex calculations and subtle signals. Extensively illustrated, Fashion in European Art explores the significance of historical dress over this period of upheaval, as well as the lived experience of dress and its representation. Drawing on visual sources that extend from paintings and photographs to fashion plates, caricatures and advertisements, the expert contributors consider how artists and their sitters engaged with the fashion and culture of their times. They explore the politics of dress, its inspirations and the reactions it provoked, as well as the many meanings of fashion in European art, revealing its importance in understanding modernity itself -- Provided by the publisher.